Neuroeducation as a Supportive Approach in Enhancing Social-Emotional Development in Early Childhood - Prengki Ade Candra (Al-Qalam Institute, 2025)
This study aims to explore how neuroeducation plays a role in supporting early childhood social-emotional development as stress management, as well as increasing children's self-awareness in learning, and social communication skills with friends in the school environment. The study is based on the importance of social-emotional skills in early childhood, which can affect their ability to interact with peers and manage emotions. The research method used is a qualitative approach with a case study design, involving interview data collection techniques, observation, and documentation with a research analysis approach according to Miles and Huberman. The findings of the study indicate that the neuroeducation program successfully helps children manage stress, increase their self-awareness, and improve social communication skills. Children involved in the program showed improvements in managing emotions, speaking confidently, and interacting more positively with peers. This study is to provide empirical evidence regarding the effectiveness of neuroeducation in developing social-emotional skills in early childhood, as well as offering a practical approach that can be applied in early childhood education institutions to support children's holistic development.